Nutrient Uptake of Fir (Abies pindrow) and Spruce (Picea smithiana) - Kaul, O. N.; Srivastava, P. B. L. (Indian Forester, 1967)
Nutrient uptake of middle-aged fir (Abies pindrow) and spruce (Picea smithiana) stands was studied with the help of plant part analysis. Representative samples of leaf, bark and wood of these species were collected from typical localities in Kashmir valley, Kulu (Himachal Pradesh) and Deoban (Uttar Pradesh) and were analysed for ash, calcium, magnesium, nitrogen, phosphorus and potassium. The results indicate that the two species do not differ much in the uptake of different nutrients in different localities.However, leaf samples of fir from Kashmir had more P and K While Ca uptake is less in wood and bark of trees from this locality. In spruce, on the other hand, Ca and N uptake are less in Deoban and Himachal Pradesh respectively. More detailed sampling on other sites and soil analysis of these localities is required to confirm the results.